2017
DOI: 10.2147/idr.s127903
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of multidrug-resistant tuberculosis among smear-positive pulmonary tuberculosis patients in Jigjiga town, Ethiopia

Abstract: BackgroundMolecular methods that target drug resistance mutations are suitable approaches for rapid drug susceptibility testing to detect multidrug-resistant tuberculosis (MDR-TB). The aim of the study was to determine MDR-TB cases and to analyze the frequency of gene mutations associated with rifampicin (RIF) and/or isoniazid (INH) resistance of Mycobacterium tuberculosis among smear-positive pulmonary tuberculosis patients.MethodsInstitution-based cross-sectional study design was employed. Sputum specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 32 publications
6
47
3
Order By: Relevance
“…42 , 43 Molecular detection of RIF resistance is used as a surrogate marker for MDR-TB. 11 , 13 , 28 Hence, the identification of RIF-resistant and MDR isolates in the present study indicated the existence of MDR-TB in the study area, which highlights the need for strengthening of the TB control program in the study area.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…42 , 43 Molecular detection of RIF resistance is used as a surrogate marker for MDR-TB. 11 , 13 , 28 Hence, the identification of RIF-resistant and MDR isolates in the present study indicated the existence of MDR-TB in the study area, which highlights the need for strengthening of the TB control program in the study area.…”
Section: Discussionmentioning
confidence: 54%
“… 47 Such type of mutation with an amino acid change of H526D was previously reported in Ethiopia in the proportion of 0%–22%. 28 , 48 , 51 , 53 The other RIF mono-resistant isolate missed rpoB WT8 and had no known mutation, which may not indicate real resistance but rather it could be due to a silent mutation in rpoB gene. 54 Similarly, such resistance was reported in previous studies of Ethiopia with various proportions including 11.8% 53 and 44.4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations